Brand Image Bellboy pada Hotel XY - Suwardiana, I Wayan Gilang; Wulan, Anak Agung Istri Ratna Sari; Sekarti, Ni Ketut (Journal of Hospitality Accommodation Management (JHAM), 2024)
This research aims to analyze the bellboy brand image at Hotel XY. The research method used in this study is a qualitative descriptive method. Data was collected by interviewing the concierge staff and observing the bellboy staff at XY. The research results show that there are still things that need to be considered in providing services to guests to make a bellboy's brand image better. The advice that can be given is that it is better to provide directions and daily briefings and refreshments regularly so that bad reviews do not occur which can affect the brand image of the bellboys at XY hotel.